Regression of Fibrosis and Liver Related Complications in Patients with Hepatitis C Who Achieved Sustained Virological Response - Sribuathong, Nattida; Bunchorntavakul, Chalermrat (Journal of The Department of Medical Services, 2023)
Background: Treatment with direct-acting antivirals (DAAs) eradicates hepatitis C virus from most patients. Information on regression of liver fibrosis and adverse outcomes is limited. Objective: The primary objective was to evaluate fibrosis changes in chronic hepatitis C (CHC) patients who achieved sustained virological response (SVR) with DAA-based therapy using transient elastography (TE). Secondary objectives were changes in non-invasive fibrosis scores; APRI and FIB-4, and liver and non-liver-related complications following SVR. Methods: This retro-prospective study was conducted at Rajavithi Hospital between June 2018 and June 2020. Consecutive CHC patients who achieved SVR with DAA were evaluated for TE, APRI, and FIB-4 under a standardized protocol at pre-treatment and follow-up periods of at least 12 months post-SVR. Fibrosis stages were categorized into F0/F1/F2/F3/F4. Fibrosis regression was defined as a reduction of the fibrosis stage after SVR. Results: Total of 104 patients were included with a mean follow-up of 20.5 (12-37) months. At pre-treatment, 74% had advanced fibrosis (F3-F4) with mean TE 18.8 kPa, FIB-4 3.4, and APRI 1.35. Following SVR, 61.5% had fibrosis regression, 35.6% had stationary fibrosis and 1.9% had fibrosis progression. Pre-treatment BMI≥25kg/m2 was significantly associated with less chance for fibrosis regression with an odd ratio of 2.34 (95%CI: 1.04, 5.25; p = .04), whereas HIV coinfection was significantly associated with a higher chance for fibrosis regression (p = .001). Two patients with de novo hepatocellular carcinoma were diagnosed at 14 and 39 months post-SVR (both had HCV genotype 3, obesity, and features of metabolic syndrome). There was no report of de novo hepatic decompensation and other significant liver and non-liver-related adverse events. Conclusion: Fibrosis regression was observed in most CHC patients after SVR and obesity was significantly associated with less chance to achieve fibrosis regression. Rare instances of de novo HCC were observed regardless of fibrosis status in which continuing surveillance should be recommended.